2012 IEEE 25th International Conference on Micro Electro Mechanical Systems (MEMS) 2012
DOI: 10.1109/memsys.2012.6170229
|View full text |Cite
|
Sign up to set email alerts
|

3-Axis acceleration switch for traumatic brain injury early warning

Abstract: This paper reports on the design, fabrication, and testing of a 3-axis acceleration switch intended to serve as an early warning for traumatic brain injury (TBI). Mild TBI (colloquially termed "concussion") resulting from rapid acceleration of the skull has been rising in the public consciousness with recently increasing awareness of the dangers and long-term health risks associated with it. The sensor described here is an array of acceleration switches designed to cover the range of acceleration associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The acceleration threshold in the horizontal direction was 255 g and the contact time was 60 μs, whereas in the vertical direction, the threshold acceleration was 75 g with a contact time of 80 μs. Currano et al [ 51 ] designed a triaxial MEMS inertial switch using a single mass–spring assembly. The device consisted of an annular mass and a centrally clamped suspension composed of four spiral springs.…”
Section: Intermittent Inertial Switchesmentioning
confidence: 99%
“…The acceleration threshold in the horizontal direction was 255 g and the contact time was 60 μs, whereas in the vertical direction, the threshold acceleration was 75 g with a contact time of 80 μs. Currano et al [ 51 ] designed a triaxial MEMS inertial switch using a single mass–spring assembly. The device consisted of an annular mass and a centrally clamped suspension composed of four spiral springs.…”
Section: Intermittent Inertial Switchesmentioning
confidence: 99%
“…ONSIDERABLE research has been directed recently for microelectromechanical systems (MEMS) inertial microswitches due to the rapid development of portable gadgets, handheld devices, and wearable technologies, combined with the emerging applications in sport, military, and automotive sectors. This is due to the attractive features of these switches, compared to the conventional mechanical inertial microswitches, which include zero power consumption at normal state, low cost, compact size, and large volume production [1][2][3][4][5][6][7][8][9][10][11]. These switches are increasingly proposed to be used in various civilian and military fields, transportation, automobiles safety, healthcare, and safety-and-arming systems.…”
Section: Introductionmentioning
confidence: 99%
“…Inertial switches based on microelectromechanical system (MEMS) usually sense shock acceleration by a movable proof mass, and the proof mass contacts a fixed electrode when the acceleration is over a given threshold. They are of great interest in many areas such as toys, accessories, automotive, military weapons, healthcare, and other shock monitoring applications [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Since Frobenius et al presented a cantilever-type electromechanical switch in 1972 [6], many studies have been done with different mechanisms: latching switch, bistable switch, tunable threshold switch, and fluidic switch in order to improve contact effect and realize higher reliability [7][8][9][10]. Besides, Currano et al reported a 3-axis acceleration switch [5] and Liu and Hao [11] and Lin et al [12] proposed a MEMS passive universal inertial switch. Although these switches achieved multidirectional detection, they have a short contact time with a rigid contact method (traditional contact method of the inertial switch), which is not conducive to signal processing for the subsequent circuit.…”
Section: Introductionmentioning
confidence: 99%